Microfinance Development in Cambodia: Challenges and a Case Study of AMK - Sophat, Phon (Thammasat Review of Economic and Social Policy, 2019)
This study aims to explore the role of microfinance institutions in Cambodia through a review of microfinance development in Cambodia focusing on the current situation and challenges faced, together with a case study of a particular microfinance institution in Cambodia. Cambodia has a rapidly developing microfinance sector with funding from domestic and international operators. Moreover, microfinance institutions represent the main providers of financial services in rural areas. Still, there are several challenges including issues concerning external funding, financial regulations and political challenges, and credit access and signs of nonperforming loans. A case study of Angkor Mikroheranhvatho Kampuchea (AMK), one of the major microfinance institutions in Cambodia, analyses access to credit for households to help understand the characteristics of AMK client and non-client households, and also to shed light on policy implications concerned with supporting financial inclusion in Cambodia.